Classification of stellar populations in globular clusters. (April 2017) - Wang, Yue; Zhao, Gang; Li, Hai-Ning
Abstract: Possessing multiple stellar populations has been accepted as a common feature of globular clusters (GCs). Different stellar populations manifest themselves with different chemical features, e.g. the well-known O−Na anti-correlation. Generally, the first (primordial) population has O and Na abundances consistent with those of field stars with similar metallicity; while the second (polluted) population is identified by their Na overabundance and O deficiency. The fraction of the populations is an important constraint on the GC formation scenario. Several methods have been proposed for the classification of GC populations. Here we examine a criterion derived based on the distribution of Galactic field stars, which relies on Na abundance as a function of [Fe/H], to distinguish first and second stellar populations in GCs. By comparing the first population fractions of 17 GCs estimated by the field star criterion with those in the literature derived by methods related to individual GCs, we find that the field star criterion tends to overestimate the first population fractions. The population separation methods, which are related to an individual GC sample, are recommended because the diversity of GCs can be taken into consideration. Currently, more caution should be exercised if one wants to regard field stars as a reference for the identification of a GC population. However, further study on the connection between field stars and GCs populations is still needed.